Chronic nicotine intake causes vascular dysregulation in the rat gastric mucosa. Issue 12 (December 1993) - Battistel, M; Plebani, M; Di Mario, F; Jocic, M; Lippe, I T; Holzer, P
Abstract : Chronic cigarette smoking has adverse effects on peptic ulcer disease because the healing of ulcers is delayed and the incidence of relapses is enhanced. Short term intake of nicotine induces vascular damage in the rat gastric mucosa, but the pathophysiological mechanisms of nicotine's action in the stomach are largely unknown. In this study rats were treated with nicotine, added to their drinking water, for 50 days. They were then anaesthetised and their stomachs perfused with acidified acetylsalicylic acid (ASA). Chronic nicotine treatment failed to change the effects of acidified ASA to induce gastric mucosal acid back diffusion, haemorrhagic damage and bleeding. Basal blood flow in the gastric mucosa was also unchanged by chronic nicotine intake, whereas the mucosal hyperaemia evoked by ASA induced acid back diffusion was averted. The concentrations of sulfidoleukotrienes were significantly augmented in the gastric wall of nicotine treated rats. These data show that chronic nicotine intake causes dysregulation of the gastric microcirculation, an effect that is associated with biochemical changes in the stomach. This study thus substantiates the adverse effects of smoking on gastric mucosal pathophysiology. These data suggest that inappropriate regulation of gastric mucosal blood flow inhibits recovery from gastric mucosal injury in smokers.